Effectiveness of ginger drink in reducing emesis gravidarum among first-trimester pregnant women - Suriyanti; Sulfianti; Mustar (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Emesis gravidarum is one of the most common discomforts experienced by pregnant women during the first trimester, characterized by nausea and vomiting that may disrupt daily activities and nutritional intake. Hormonal changes, particularly increased levels of estrogen, progesterone, and human chorionic gonadotropin (hCG), play a significant role in the onset of these symptoms. Ginger is widely recognized as a natural remedy with antiemetic properties, thanks to its active compounds, including gingerol, shogaol, and essential oils, which help suppress the vomiting reflex and promote gastrointestinal comfort. This study aims to determine the effectiveness of ginger drink in reducing emesis gravidarum among pregnant women in the first trimester. Methods: This research employed a quantitative approach with a quasi-experimental one-group pretest–posttest design. The study was conducted in the working area of BLUD UPT Puskesmas Cina, involving 25 pregnant women in their first trimester who experienced emesis gravidarum. Respondents received a ginger drink intervention, and measurements of nausea and vomiting frequency and severity were collected before and after the intervention. Data were analyzed using statistical tests to determine significant differences. Results: The findings revealed a significant reduction in nausea and vomiting after regular consumption of a ginger drink. Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a statistically significant difference between pre- and post-intervention scores. The results support the alternative hypothesis that ginger drink effectively reduces symptoms of emesis gravidarum. Conclusion: Ginger drink is proven to be an effective, safe, and accessible non-pharmacological intervention for reducing emesis gravidarum in first-trimester pregnant women. Its use can serve as an alternative therapy before pharmacological treatment, supporting maternal comfort and well-being.